2008
DOI: 10.1103/physrevd.77.084007
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical issues in a fully constrained formulation of the Einstein equations

Abstract: Bonazzola, Gourgoulhon, Grandclément, and Novak [Phys. Rev. D 70, 104007 (2004)] proposed a new formulation for 3+1 numerical relativity. Einstein equations result, according to that formalism, in a coupled elliptic-hyperbolic system. We have carried out a preliminary analysis of the mathematical structure of that system, in particular focusing on the equations governing the evolution for the deviation of a conformal metric from a flat fiducial one. The choice of a Dirac's gauge for the spatial coordinates gua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 45 publications
0
63
0
Order By: Relevance
“…The analysis in [18] concludes that the reason behind the failures in these axisymmetric formulations is in fact related to the presence of wrong signs or, more precisely, to the indefinite character of certain non-linear Helmholtzlike equations present in the scheme (see [18] for details and also for a parallel numerical discussion in terms of a class of relaxation methods for the convergence of the elliptic solvers). Regarding the full three-dimensional case, fully constrained formalisms have been presented in [23,24,25]. While the work in [23,24] includes an elliptic subsystem closely related to the XCTS equations and therefore suffers potentially from these nonuniqueness problems, the uniqueness properties of the scheme of [25] must yet be studied.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis in [18] concludes that the reason behind the failures in these axisymmetric formulations is in fact related to the presence of wrong signs or, more precisely, to the indefinite character of certain non-linear Helmholtzlike equations present in the scheme (see [18] for details and also for a parallel numerical discussion in terms of a class of relaxation methods for the convergence of the elliptic solvers). Regarding the full three-dimensional case, fully constrained formalisms have been presented in [23,24,25]. While the work in [23,24] includes an elliptic subsystem closely related to the XCTS equations and therefore suffers potentially from these nonuniqueness problems, the uniqueness properties of the scheme of [25] must yet be studied.…”
Section: Introductionmentioning
confidence: 99%
“…First, it is shown that imposing the Dirac gauge in (1) indeed guarantees the real character of the eigenvalues corresponding to matrices A i , and therefore the hyperbolicity of the evolution system. Of particular relevance for the present inner BC discussion is the explicit determination of the (non-vanishing) characteristic speeds associated with the vector s normal to the excision surface S t , resulting in [7] λ (s) ± = −β ⊥ ± N (each one of multiplicity 6). (10) Taking into account the inequality in (4), consequence of the choice of a coordinate system adapted to the DH H by enforcing condition (6), we conclude the absence of ingoing radiative modes into the integration domain Σ t at the excision surface.…”
Section: Ii) Gauge Conditions For the Tangential Part Of The Shiftmentioning
confidence: 99%
“…For this reason, we rather adopt the methodological choice of only prescribing MOTS as inner BCs. Regarding a possible FOTH condition failure, and according with the characteristic analysis in [7], monitoring the sign of (β ⊥ − N ) determines if inner BCs must or must not be provided for the radiative modes. This work represents an intermediate step in the ongoing program [6] addressing fullyconstrained excised black hole numerical evolutions.…”
Section: Ii) Gauge Conditions For the Tangential Part Of The Shiftmentioning
confidence: 99%
See 2 more Smart Citations